The Cost of Health Care in Maine: “It All Depends” - Bryant, Daniel (Maine Policy Review, 2025)
When policymakers consider reform of Maine’s healthcare system to reduce costs for Maine residents, it is important for them to compare those residents’ total costs in the reform proposed with their current total costs. The latter include both hidden costs, which I addressed in a previous commentary, and apparent costs, which I address here. Using the same example of a hypothetical 30-year-old Maine resident, I examine the total apparent costs that individual might bear for a range of healthcare expenses in six different healthcare coverage options: no insurance (self-pay), commercial insurance obtained through the Maine Health Insurance Marketplace, two instances of a workplace health benefit, and two of a state-based, publicly funded, universal healthcare plan (single payer). I conclude that Mainers’ healthcare costs vary greatly with the type of coverage they have and that when these costs exceed $1,500 to $2,000 a year, the single-payer model would cost this hypothetical Maine resident, and presumably many other Mainers, less than they pay now regardless of their current type of coverage.
Keywords: single-payer health care plan; health insurance; medical care